A New Development Approach of Intelligent Monitoring System for Library Pioneers Behavior Based on University Regulations - Sabri Salim, Muhammed (International Journal of Engineering and Technology, 2018)
The modern technology of video surveillance systems has proved to be the best solution in direct supervision of property, individuals, and the environment. This article addresses the design approach of a smart surveillance system for university library to ensure compliance with library usage rules. The solution proposed for the surveillance system depends on innovative integration of intelligent algorithm, cameras and motion detectors in the web application. An algorithm was created according to the instructions of attending the university library of Al-Nahrain University. This algorithm has the ability to analyze video and extract the effectiveness that does not comply with the library's rules and regulations that the student can do in the library. The PX1-C415 Single Board Computer type is programmed with a smart algorithm and integrated with motion detectors and video cameras to create the proposed system. It has ability for detection, processing and rapid response through capturing images and transferring them to a wireless module on the administrative desk and thus activating the alarm system. The accuracy of the detection algorithm used was 91% for a distance of 1-5 meters. In addition, the admin received the violations with accuracy of 93%. The proposed system offers a perfect solution that is accurate, fast and scalable to support comprehensive and economical monitoring.Â Â